5n+6p+7n+p=

Simple and best practice solution for 5n+6p+7n+p= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n+6p+7n+p= equation:


Simplifying
5n + 6p + 7n + p = 0

Reorder the terms:
5n + 7n + 6p + p = 0

Combine like terms: 5n + 7n = 12n
12n + 6p + p = 0

Combine like terms: 6p + p = 7p
12n + 7p = 0

Solving
12n + 7p = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7p' to each side of the equation.
12n + 7p + -7p = 0 + -7p

Combine like terms: 7p + -7p = 0
12n + 0 = 0 + -7p
12n = 0 + -7p
Remove the zero:
12n = -7p

Divide each side by '12'.
n = -0.5833333333p

Simplifying
n = -0.5833333333p

See similar equations:

| (n+3)*9=45 | | (n-8)*6=30 | | x^2+12x-25=0 | | -2+-2=-2(x-5)-6 | | 77-3x=24x+14 | | 5x+35=14x-36 | | 1+2[3(x-1)-5(2x-3)]=2x-7 | | 4x+5-10x=8+3x+12 | | 5x+31=tx+11 | | 4x^2+7x-8=0 | | 8b-4(b-2)=42 | | -6-20=-2n | | 2x+10=110-10x | | 8x+9=2x-13 | | 4x=8x+6 | | x+4+5+2=3+2+2x | | 2*(x+3)-3(x+1)=x-13 | | b(b+2)+4b^2=5b^2+9b+8 | | 10x-13=3x-7 | | y=2x^3-7x^2-15x | | x+11=8+x | | x+11=8+c | | n-9=7 | | n+27=44 | | a-4=3a-6 | | 5y-10=2y-3x+11 | | (11x)=(5x+30) | | 2x+8=8x-1 | | 51-81.623= | | 0=(.25x^4)-(2x^2)-1 | | 7.2g+1.5=6+3.2g | | 2x^2+4x-10=0 |

Equations solver categories